Study on the Calculation Method of the Diffusion Range of Grouting Slurry for a High-speed Railway Ballastless Track Subgrade - Changwei Yang; Jinhao Guo; Shaowei Wei; Liang Zhang; Sifeng Li; Yang Liu (Advances in Civil Engineering)
Grouting engineering is the most convenient and quick way to deal with postconstruction settlement. Based on the investigation of the Beijing Shenyang high-speed railway in the early stage, the microdestructive force of grout on the soil mass in the process of grouting with the method of fluid solid coupling theory was analyzed. The numerical simulation results show that, in the grouting process, the greater the grouting pressure, the wider the diffusion range of the slurry and the greater the damage to the microscopic contact force of the slurry to the soil; in addition, when the grouting pressure is below 0.15 MPa, the diffusion form of the slurry in the soil is osmotic grouting; when the pressure is about 0.3 MPa, the diffusion form of the slurry in the soil is compacted grouting; on the basis of the simulation results, a deeper research is carried out, and the calculation formula of the slurry diffusion curve is obtained. It fills in the blank of the theoretical study of the slurry diffusion curve. In this paper, the diffusion formula of grouting slurry can be used in the theoretical study of clay grouting, and it can be used as a reference for practical engineering.